The Effect of Acid-Reducing Pharmacotherapy on the Severity of Nausea and Vomiting of Pregnancy - Simerpal Kaur Gill; Caroline Maltepe; Katayoon Mastali; Gideon Koren (Hindawi Limited, 2009)
Background. Heartburn and acid reflux (HB/RF) are associated with increased severity of nausea and vomiting. The ability of acid-reducing drugs to reduce symptoms of nausea and vomiting of pregnancy has not been previously tested. Objective. To determine whether acid-reducing pharmacotherapy decreases the severity of NVP symptoms. Methods. We studied a cohort of women experiencing NVP, who were also experiencing HB/RF. Women were counseled to commence acid-reducing pharmacotherapy. The effectiveness of the acid-reducing medication in decreasing symptoms of both HB/RF and NVP was measured. Results. Acid-reducing drugs resulted in significant decreases in PUQE (9.6±3.0 to 6.5±2.5, P<.0001) and well-being scores from the initial (4.0±2.0) to the follow-up interview (6.8±1.6, P<.0001). After intervention with acid-reducing pharmacotherapy, a reduction in acid symptoms correlated significantly with reduction in NVP (R2=0.72, P<.001). Conclusion. This is the first study to demonstrate that management of HB/RF can reduce the severity of NVP.